Drought propagation in high-latitude catchments: insights from a 60-year analysis using standardized indices - C. Teutschbein; T. Grabs; M. Giese; A. Todorović; R. Barthel (Natural Hazards and Earth System Sciences)
Droughts, traditionally less associated with high-latitude regions, are emerging as significant challenges due to changing climatic conditions. Recent severe droughts in Europe have exposed the vulnerability of northern catchments, where shifts in temperature and precipitation patterns may intensify drought impacts. This study investigates the dynamics of drought propagation in high-latitude regions, focusing on four key aspects: (1) the typical lag time for drought conditions to propagate from initial precipitation deficits to impacts on soil moisture, streamflow, and groundwater systems; (2) the probability of precipitation deficits leading to these droughts; (3) the key catchment characteristics influencing drought propagation; and (4) the way in which drought propagation has evolved under changing climate conditions. By analyzing long-term observational records from 50 Swedish catchments, the study reveals that drought propagation is highly variable and influenced by a complex interplay of catchment characteristics, hydroclimatic conditions, and soil properties. Soil moisture exhibits the shortest propagation times, often responding within a month to precipitation deficits, while groundwater shows the longest and most variable response times, sometimes exceeding several months. The probability of precipitation deficits propagating into soil moisture droughts is highest, followed by streamflow and groundwater, with these probabilities increasing over time. Across all drought types, annual precipitation and streamflow emerge as the most influential factors governing both propagation time and probability. Although most catchments have become wetter year-round due to climate change, southern catchments are increasingly vulnerable to spring droughts (particularly soil moisture drought), driven by increasing evaporative demand. Despite these hydroclimatic shifts, no significant long-term trends in propagation times or probabilities have been observed over the past 60 years. These findings highlight the need for tailored region-specific water management strategies to address seasonal and regional variations in drought risks, particularly as climate change continues to reshape hydrological regimes.